Best Practices for Probiotic Research in Athletic and Physically Active Populations: Guidance for Future Randomized Controlled Trials - Mohr, Alex E.; Pugh, Jamie; O'Sullivan, Orla; Black, Katherine; Townsend, Jeremy R.; Pyne, David B.; Wardenaar, Floris C.; West, Nicholas P.; Whisner, Corrie M.; McFarland, Lynne V. (Frontiers in Nutrition, 2022)
Probiotic supplementation, traditionally used for the prevention or treatment of a variety of disease indications, is now recognized in a variety of population groups including athletes and those physically active for improving general health and performance. However, experimental and clinical trials with probiotics commonly suffer from design flaws and different outcome measures, making comparison and synthesis of conclusions difficult. Here we review current randomized controlled trials (RCTs) using probiotics for performance improvement, prevention of common illnesses, or general health, in a specific target population (athletes and those physically active). Future RCTs should address the key elements of 1) properly defining and characterizing a probiotic intervention, 2) study design factors, 3) study population characteristics, and 4) outcome measures, that will allow valid conclusions to be drawn. Careful evaluation and implementation of these elements should yield improved trials, which will better facilitate the generation of evidence-based probiotic supplementation recommendations for athletes and physically active individuals.